'We are not going to educate people': how students negotiate engineering identities during collaborative problem solving. (4th July 2021) - Khosronejad, Maryam; Reimann, Peter; Markauskaite, Lina
ABSTRACT: Professional identity development is central to engineering education and has been an important focus of design for learning. However, little is known about how learners develop different aspects of engineering identity in response to the constraints and enablements of their learning environment. The purpose of this paper is to propose an analytical approach for the exploration of how the learning environment facilitates engineering professional identity practices. We illustrate the application of the Implied Identity approach by looking at a group of four engineering students working collaboratively on a task about sustainability. We apply conversation analysis for an in-depth investigation of students' talk to explore how engineering identities are negotiated. Results show that the group's collaborative processes involve their identification with the engineering profession by excluding aspects of other professions from the (professional) self. This process is mediated by implied identities that are negotiated by participants. Applying this approach enables one to investigate the interplay between learner and learning environment and highlights the role of individuals' agency in relation to the contextual effects.